The role of alpha-helix on the structure-targeting drug design of amyloidogenic proteins - Tempra, Carmelo; La Rosa, Carmelo; Lolicato, Fabio (Chemistry and physics of lipids, 2021)
The most accredited hypothesis links the toxicity of amyloid proteins to their harmful effects on membrane integrity through the formation of prefibrillar-transient oligomers able to disrupt cell membranes. However, damage mechanisms necessarily assume a first step in which the amyloidogenic protein transfers from the aqueous phase to the membrane hydrophobic core. This determinant step is still poorly understood. However, according to our lipid-chaperon hypothesis, free lipids in solution play a crucial role in facilitating this footfall. Free phospholipid concentration in the aqueous phase acts as a switch between ion channel-like pore and fibril formation, so that high free lipid concentration in solution promotes pore and repress fibril formation. Conversely, low free lipids in the solution favor fibril and repress pore formation. This behavior is due to the formation of stable lipid-protein complexes. Here, we hypothesize that the helix propensity is a fundamental requirement to fulfill the lipid-chaperon model. The alpha-helix region seems to be responsible for the binding with amphiphilic molecules fostering the proposed mechanism. Indeed, our results show the dependency of protein-lipid binding from the helical structure presence. When the helix content is substantially lower than the wild type, the contact probability decreases. Instead, if the helix is broadening, the contact probability increases. Our findings open a new perspective for in silico screening of secondary structure-targeting drugs of amyloidogenic proteins.